Prevention of inflammatory complications after removal of tumors and of tumor-like diseases of the jaws - Tymofieiev, O.; Ushko, N. (Actual Dentistry, 2018)
Purpose: to determine the effectiveness of using the preparation «Tantum Verde®» for the prevention and treatment of postoperative complications in patients after intraoral approach removal of tumor-like formations and jaw tumors. Methods. 88 patients were examined at the age of 18 to 74 years after intraoral surgery on the upper and lower jaws about removing radicular cysts, epulidis, osteoblastomas and ameloblastomas. Results. Based on examination of patients after surgical interventions on the jaws, which are made intraoral method, it can be concluded that the preparation «Tantum Verde®» are highly effective in common use for the hygienic care of the oral cavity in the postoperative period. Conclusions. The use of preparation «Tantum Verde®» and has reduced the number of postoperative complications by 4.5 times at examined patients. Key words: tumors of the jaws, tumor-like diseases of the jaws, pain, inflammation, postoperative complications, Tantum Verde®.